Prediction model and its application of helium extraction OPEX based on response surface methodology - Yiping Wu; Shen'aoyi Liu; Qing Wang; Rong Chen; Yuanyuan He; Li Fu; Wanting Li; Ruiyi Yang (Heliyon, 2024)
Focusing on the situation of the low helium content in natural gas resource in China and the high cost of helium extraction, the OPEX prediction model of helium extraction that based on the Response Surface Methodology (RSM) is proposed. This method applies ASPEN-HYSYS software to simulate the helium extraction process flow for a given product composition, pressure, and temperature; Applying the Design Expert module for Response Surface Methodology(RSM) parameter design, combined with OPEX of existing projects, determine the key influencing factors and upper and lower limits of OPEX, and obtaining the corresponding OPEX for different parameter values; Applying the Box Behnken Design (BBD) principle to optimize the helium extraction process parameters of RSM, based on fitting results and parameter significance verification of second-order regression function, the OPEX prediction model is built.This method is applied to a domestic helium extraction project, and the unit helium extraction cost is between 100 and 119.52 yuan/m3, IRR is 13.37%. The result shows the project has economic benefit, and the method presents a good perspective application.